Effect of China national centralized drug procurement policy on anticoagulation selection and hemorrhage events in patients with AF in Suining - Zhang, Qi; Wang, Ruili; Chen, Lei; Chen, Wensu (Frontiers in Pharmacology, 2024)
Background: Launched in March 2019, the National Centralized Drug Procurement (NCDP) initiative aimed to optimize the drug utilization framework in public healthcare facilities. Objective: This study aims to comprehensively assess the impact of the NCDP policy on the efficacy of anticoagulation therapy, patient medication adherence, and the incidence of hemorrhagic events in individuals with non-valvular atrial fibrillation (NVAF) residing in Suining. Methods: This study analyzed patient hospitalization records from the Department of Cardiology at Suining County People's Hospital, spanning January 1, 2017, to June 30, 2022. The dataset included demographic details (age, sex), type of health insurance, year of admission, hospitalization expenses, and comprehensive information on anticoagulant therapy utilization. The CHA2DS2-VASc scoring system, an established risk assessment tool, was used to evaluate stroke risk in NVAF patients. Patients with a CHA2DS2-VASc score of 2 or higher were categorized as high-risk, while those with scores below 2 were considered medium or low risk. Results: 1. Overall, oral anticoagulant use increased from 40.02% to 61.33% post-NCDP (P < 0.001). Specifically, NOAC utilization among patients dramatically rose from 15.41% to 90.99% (P < 0.001). 2. There was a significant decrease in hemorrhagic events following the NCDP policy, from 1.88% to 0.66% (P = 0.01). 3. Among the 219 patients requiring re-hospitalization, there was a notable increase in anticoagulant usage post-NCDP, from 36.07% to 59.82% (P < 0.001). NOACs, in particular, saw a substantial rise in usage among these patients, from 11.39% to 80.92% (P < 0.001). 4. The NCDP policy [OR = 28.223, 95% CI (13.148, 60.585), P < 0.001] and bleeding events [OR = 27.772, 95% CI (3.213, 240.026), P = 0.003] were significant factors influencing the alteration of anticoagulant medications in patients. Conclusion: The NCDP policy has markedly improved anticoagulation management in patients with AF. This policy has played a crucial role in enhancing medication adherence and significantly reducing the incidence of hemorrhagic events among these patients. Additionally, the NCDP policy has proven to be a key factor in guiding the selection and modification of anticoagulant therapies in the AF patient population.